2020
DOI: 10.1002/ams2.501
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategies for ischemia reperfusion injury in emergency medicine

Abstract: Ischemia reperfusion (IR) injury occurs when blood supply, perfusion, and concomitant reoxygenation is restored to an organ or area following an initial poor blood supply after a critical time period. Ischemia reperfusion injury contributes to mortality and morbidity in many pathological conditions in emergency medicine clinical practice, including trauma, ischemic stroke, myocardial infarction, and post-cardiac arrest syndrome. The process of IR is multifactorial, and its pathogenesis involves several mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 65 publications
1
50
0
1
Order By: Relevance
“…Hydrogen represents an effective and non‐toxic molecule with wide potential for treating various diseases associated with oxidative injury, including transplantation‐related organ damage 24,25 . Protective mechanisms have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen represents an effective and non‐toxic molecule with wide potential for treating various diseases associated with oxidative injury, including transplantation‐related organ damage 24,25 . Protective mechanisms have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Whether through thrombosis formation or respiratory deficiency, the hypoxic state can lead to organ and tissue injury. Furthermore, the restoration of oxygen to tissues (especially when a patient is placed on mechanical ventilation) can give rise to reperfusion injury [ 76 , 150 ]. A few earlier studies have demonstrated that ET is protective in tissues exposed to ischemia-reperfusion injury.…”
Section: How Might Ergothioneine Be Beneficial In Alleviating Covimentioning
confidence: 99%
“…[ 21 ] IRI damage to the microvasculature can continue to reduce blood flow to the ischemic tissue, leading to the “no-reflow phenomenon.”[ 22 ] Many therapies have been introduced to combat IRI including but not limited to edaravone, vitamins, therapeutic hypothermia, and NO. [ 23 ] Studies show that NO and its derivatives such as inhaled NO, nitrites, and peroxynitrite modulate IRI of the myocardium. [ 24 ] For this review, we will examine the various NO derivatives and their efficacy in modulating MIs.…”
Section: The Clinical Trials Of Nitric Oxide In Myocardial Infarctionmentioning
confidence: 99%